2018
DOI: 10.15381/rivep.v29i4.15346
|View full text |Cite
|
Sign up to set email alerts
|

Neosporosis en alpacas de la provincia de Huaytará, Huancavelica, Perú

Abstract: El objetivo del estudio fue determinar la seroprevalencia de anticuerpos de N. caninum, mediante la técnica de Inmunofluorescencia Indirecta (IFI), empleando un punto de corte de 1:100, en 288 alpacas de varios centros poblados de la provincia de Huaytará, departamento de Huancavelica, durante 2016 y 2017. Se colectaron muestras de sangre y se levantó información situacional y epidemiológica de los rebaños muestreados. La seroprevalencia fue de 16.3 ± 4.3% (47/288), sin diferencias significativas por efecto de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, nothing is known about the efficiency of vertical transmission of N. caninum in SAC or about the meaning of horizontal transmission through the ingestion of sporulated oocysts shed by canids in these animal species. In Peru, no significant association was found between seropositivity to N. caninum in SAC and age [55,56] or geographical region [57], suggesting that the infection might be mainly transmitted vertically [57]. Apart from some regional studies from Peru, in which higher seroprevalences of infection were reported (17.9-42.4 % in alpacas and 18.4-23.3% in llamas) [58,59], only low seroprevalences were observed in studies outside South America, suggesting that only few animals had contact with the parasite.…”
Section: Discussionmentioning
confidence: 79%
“…However, nothing is known about the efficiency of vertical transmission of N. caninum in SAC or about the meaning of horizontal transmission through the ingestion of sporulated oocysts shed by canids in these animal species. In Peru, no significant association was found between seropositivity to N. caninum in SAC and age [55,56] or geographical region [57], suggesting that the infection might be mainly transmitted vertically [57]. Apart from some regional studies from Peru, in which higher seroprevalences of infection were reported (17.9-42.4 % in alpacas and 18.4-23.3% in llamas) [58,59], only low seroprevalences were observed in studies outside South America, suggesting that only few animals had contact with the parasite.…”
Section: Discussionmentioning
confidence: 79%